World social protection report 2017-2019 : universal social protection to achieve sustainable development goals - International Labour Office. International Pogramme on the Elimination of Child Labour; International Labour Organisation. Administrative Tribunal (Geneva International Labour Organization (ILO), 2017)
​Universal social protection is essential for realizing the human right to social security for all, advancing social justice and promoting inclusive growth, and accelerating progress towards achieving the globally agreed 2030 Agenda for Sustainable Development and its Sustainable Development Goals (SDGs). This ILO flagship report provides a global overview on recent trends in social protection systems, including social protection floors. Based on new data, it offers a broad range of global, regional and country data on social protection coverage, benefits and public expenditures on social protection. (ILO)
Preface -- Executive summary -- 1. Introduction -- 2. Social protection for children -- 3. Social protection for women and men of working age -- 4. Social protection for older women and men. Fighting poverty through pension systems -- 5. Towards universal health coverage -- 6. Monitoring progress in social protection: Regional trends -- 7. Monitoring progress in social protection: Global outlook -- ANNEXES -- Bibliography
ILO flagship report
Includes bibliographical references (p.415-431)
Keywords: Insurance; SOCIAL SECURITY; RIGHT TO SOCIAL SECURITY; SOCIAL POLICY; ECONOMIC DEVELOPMENT; SUSTAINABLE DEVELOPMENT; PENSIONS; ILO Declarations